PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV MI HUBBUL WATHAN RIMBA MELINTANG KECAMATAN RIMBA MELINTANG - Fairus Murni; Lazim N '; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Latar of behind this research is lowering nya of result of learning IPA of student of class of Athwart IV MI Hubbul Wathan Jungle. While Complete Criterion value Minimize the ( KKM) IPA is 70. Among/Between student amounting to 20 people only 5 one who reach the KKM. This Research represent the Research of Class Action ( PTK) which aim to to increase result of learning IPA of student of class of Athwart IV MI Hubbul Wathan Jungle by applying model the study of co-operative of type of Two Stay Two Stray ( TSTS). Instrument of data collecting of at this sikripsi is activity sheet learn and student and also result of learning. This Sikripsi present the data of result of learning obtained from flattening- flatten the result learn before action 59,50 mounting 13,75 becoming 73,25 at cycle 1. At cycle II mount to become 11 with the mean 84,25. Activity learn at cycle 1 first meeting obtain;get the percentage 57,50% with the category enough, at second meeting experience of the improvement with the percentage 65% good category, and hereinafter at first cycle II meeting of activity learn also experience of the improvement with the percentage 75% good category. And at second cycle II meeting mount again with the percentage 90% with the category very good. Student activity of at cycle 1 first meeting obtain;get the percentage 55% with the category enough. At meeting two experiencing of improvement 57,50% with the category enough. At this cycle is student have started to comprehend the study activity by applying model the study of co-operative of type TSTS marked with the student activity of at first cycle II meeting mount with the percentage 77,50% with the category of baik.Pada meeting two cycle ii experience of the make-up of percentage 85% with the category very good. Result of research in class IV prove that applying model the study of co-operative of type TSTS can improve the result learn the student of class IV.Keyword: Applying model the study of co-operative of type TSTS, Result of learning